THE METAL COMPLEXES OF 1-(PHENYLAMINO)-4, 4, 6-TRIMETHYL-3, 4-DIHYDROPYRIMIDINE-2-(1H)-THIONE: PREPARATION, PHYSICAL, SPECTROSCOPIC STUDIES AND ANTIBACTERIAL PROPERTIES - Khare, Rajshree; Sethi, Pooja (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: The metal complexes of 1-(Phenylamino)-4, 4, 6-trimethyl-3, 4-dihydropyrimidine-2-(1H)-thione: preparation, physical and spectroscopic studies and preliminary antibacterial properties. Methods: Complexes of bidentate ligand containing N, S-bridge [M(pmpt)2(H2O)n] (M(II) = Cu, Mn, Ni, Co; n = 2 and M(II) = Zn, Cd, Pd; n = 0) derived from the reaction of Hpmpt ligand with metals (M(II) = Cu, Mn, Ni, Co, Zn, Cd, Pd) and characterized by various physico-chemical techniques. From magnetic moment studies, square planar geometry is suggested for Zn(II), Cd(II), Pd(II) complexes, octahedral geometry is proposed for Co(II), Ni(II) and Mn(II) and distorted octahedral for Cu(II) complexes. Thermo gravimetric (TG) curves indicate the decomposition of complexes in four to five steps. The presence of coordinated water in metal complexes was confirmed by thermal, elemental analysis and IR data. Free ligand and its complexes were assayed in vitro for their antibacterial activity against gram positive and gram negative bacteria using chloramphenicol as a standard market-drug. Results: The reported complexes were synthesized through greener protocol that is grindstone method by mixing the ligand and metal salts in 2:1 molar ratio. Products were obtained in good yield with sharp melting point. Conclusion: Studies have indicated that such complexes can be prepared by environment friendly approach which requires less time, simple workup for isolation and purification with good yield. The [Ni(pmpt)2(H2O)2] complex showed excellent antibacterial activity while other reported metal complexes showed weak antibacterial activity. Â 